Molecular characterization of candidate markers for callogenesis in oil palm (elaeis guineensis jacq.) - Conie, Toh (2014)
Cloning of oil palm via micropropagation technique enables the improvement of planting materials using existing individuals which have most of the desired qualities such as good oil yield and composition, small height increment, drought tolerance and disease resistance. Cloning also circumvent the long generation time required with conventional breeding techniques to generate high quality elite oil palm planting material. Usually, oil palm micropropagation is performed by inducing somatic embryogenesis on calli derived from leaf tissue. However, the callogenesis rate in oil palm is very poor. A previous study had successfully isolated and identified differentially expressed sequences during oil palm callogenesis using representational difference analysis (RDA) approach. These differentially expressed sequences are potential candidate markers for oil palm callogenesis. As such, they can be used for screening explants with high callusing rates. Early identification would enable reductions in time and costs in the micropropagation process. Prior to that, these markers had to be characterized first in order to determine their applicability in predicting tissues that have potential in callusing. As such, eight candidate markers were selected for full length cDNA isolation and molecular characterization, namely gibberellin regulated protein (EgGA), nuclear transcription factor Y subunit C (EgNTF), integral membrane family protein (EgIMP), hypothetical protein (EgHypothetical), glutathione S-transferase (EgGST), glycine-rich RNA-binding protein (EgGRP), ATP-dependent Clp protease (EgClpP) and early nodulin 93 protein (EgENOD). Real time RT-PCR indicated that overall, the transcripts were found to be preferentially expressed in tissue culture derived materials from leaf (leaf explant, embryogenic callus, non-embryogenic callus, cell suspension culture, globular, haustorium and germinating embryoid) and relatively low levels in non-tissue culture derived materials (female flower, male flower, meristem and root). The expression analysis via real time RT-PCR using various leaf explants samples also indicated that four out of eight markers (EgGA, EgHypothetical, EgGST and EgClpP) had different expression pattern between the low and highly callusing tissues at certain stages, which indirectly showed that it has the capability in differentiating both tissues and thus, were characterized further via RNA in situ hybridization. Interestingly, all of the four markers appeared to have display a tissue-specific expression pattern. In conclusion, the expression patterns of all of the eight calla genesis-related transcripts are considered to be stage-dependent and genotype-specific, and are postulated to play significant roles at different stages of oil palm callogenesis. A regression model for callogenesis with a predictive accuracy of 21.6% was constructed for the EgClpP expression marker. It may be interesting to further explore EgClpP expression profiles across a wider range of oil palm genotypes in order to confirm the suitability as putative marker for screening ortets that are amenable to tissue culture.